Security policy monitoring of BPMN‐based service compositions. Issue 9 (22nd February 2018) - Asim, Muhammad; Yautsiukhin, Artsiom; Brucker, Achim D.; Baker, Thar; Shi, Qi; Lempereur, Brett
Abstract: Service composition is a key concept of Service‐Oriented Architecture that allows for combining loosely coupled services that are offered and operated by different service providers. Such environments are expected to dynamically respond to changes that may occur at runtime, including changes in the environment and individual services themselves. Therefore, it is crucial to monitor these loosely coupled services throughout their lifetime. In this paper, we present a novel framework for monitoring services at runtime and ensuring that services behave as they have promised. In particular, we focus on monitoring non‐functional properties that are specified within an agreed security contract. The novelty of our work is based on the way in which monitoring information can be combined from multiple dynamic services to automate the monitoring of business processes and proactively report compliance violations. The framework enables monitoring of both atomic and composite services and provides a user friendly interface for specifying the monitoring policy. We provide an information service case study using a real composite service to demonstrate how we achieve compliance monitoring. The transformation of security policy into monitoring rules, which is done automatically, makes our framework more flexible and accurate than existing techniques.